Innovative Dual-Functional Photocatalyst Design for Precision Water Remediation - Yike Li; Xian Liu (Crystals)
This study pioneers the development of a synergistic Ag-doped molecularly imprinted TiO2 photocatalyst (MIP-Ag-TiO2) through a multi-strategy engineering approach, integrating molecular imprinting technology with plasmonic metal modification via a precisely optimized sol–gel protocol. Breaking from conventional non-selective photocatalysts, our material features an engineered surface architecture that combines selective molecular recognition sites with enhanced charge separation capabilities, specifically tailored for the targeted degradation of recalcitrant salicylic acid (SA) contaminants. Advanced characterization (XRD, EPR, FT-IR, TEM-EDS) reveals unprecedented structure–activity relationships, demonstrating how template molecule ratios (Ti:SA = 5:1) and calcination parameters (550 °C) collaboratively optimize both adsorption selectivity and quantum efficiency. The optimized MIP-Ag-TiO2 achieves breakthrough performance metrics: 98.6% SA degradation efficiency at 1% Ag doping, coupled with a record selectivity coefficient R = 7.128. Mechanistic studies employing radical trapping experiments identify a dual •OH/O2−-mediated degradation pathway enabled by the Ag-TiO2 Schottky junction. This work establishes a paradigm-shifting “capture-and-destroy” photocatalytic system that simultaneously addresses the critical challenges of selectivity and quantum yield limitations in advanced oxidation processes, positioning molecularly imprinted plasmonic photocatalysts as next-generation smart materials for precision water purification.